2009
DOI: 10.1097/hjh.0b013e328329bbd7
|View full text |Cite
|
Sign up to set email alerts
|

Role of anandamide transporter in regulating calcitonin gene-related peptide production and blood pressure in hypertension

Abstract: Decreased plasma CGRP level in patients with essential hypertension or SHRs is likely due to the reduced AEA transporter activity, and the increased ADMA level may account for the reduced AEA transporter activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 38 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…However, Lu et al [52] observed that the ADMA level in serum is increased more in aged (24 months) rats than in young animals (six months), but in their study no difference in mRNA expression for CGRP in ADMA-treated rats was noted. In contrast, CGRP production was decreased in spontaneously hypertensive (SHR) rats and this effect was accompanied by elevated plasma levels of ADMA [53]. In our present study, the supplementation of ADMA-treated rats with exogenous CGRP attenuated I/R-induced gastric lesions potentiated by ADMA and reversed in part, the accompanying decrease in GBF and plasma CGRP levels in rats with or without capsaicin denervation in the presence of ADMA.…”
Section: Resultsmentioning
confidence: 44%
“…However, Lu et al [52] observed that the ADMA level in serum is increased more in aged (24 months) rats than in young animals (six months), but in their study no difference in mRNA expression for CGRP in ADMA-treated rats was noted. In contrast, CGRP production was decreased in spontaneously hypertensive (SHR) rats and this effect was accompanied by elevated plasma levels of ADMA [53]. In our present study, the supplementation of ADMA-treated rats with exogenous CGRP attenuated I/R-induced gastric lesions potentiated by ADMA and reversed in part, the accompanying decrease in GBF and plasma CGRP levels in rats with or without capsaicin denervation in the presence of ADMA.…”
Section: Resultsmentioning
confidence: 44%
“…Since numerous endocannabinoid-like compounds were changed in hypertensive animals, future studies should clarify whether these compounds affect the cardiovascular system. As suggested previously [49], the enhanced levels of AEA, LEA, OEA and SEA (all of which are degraded by FAAH) in spite of higher FAAH activity might indicate that in the heart of the DOCA group endocannabinoid synthesis is favoured [61] and/or AEA transporter activity is decreased [62].…”
Section: Effect Of Hypertensionmentioning
confidence: 61%
“…The endocannabinoid system is suggested to buffer increases in BP in hypertension. In support of this, the plasma level of the best known endocannabinoid, anandamide (AEA), was higher in hypertensive patients (Engeli et al , ) and in spontaneously hypertensive rats (SHR; Li et al , ). Moreover, in acute experiments, (1) the CB receptor‐mediated hypotension elicited by AEA was stronger in anaesthetized SHR than in normotensive controls (Lake et al , ; Bátkai et al , ); (2) in conscious SHR, AEA decreased BP, but increased it in normotensive controls (Lake et al , ); and (3) the systemic acute blockade of fatty acid amide hydrolase (FAAH; the key enzyme responsible for AEA degradation) by URB597 (Bátkai et al , ) and AM3506 (Godlewski et al , ) has been shown to normalize BP in SHR.…”
Section: Introductionmentioning
confidence: 93%